Citations as a currency: Every performance measure creates its own behaviour. Issue 2 (May 2015) - Oppewal, Harmen
Abstract This commentary discusses how citations, when adopted as benchmarks, influence publication and assessment behaviours of researchers and institutions. It compares benchmarking based on Google Scholar with current research assessment practices, as exemplified by the ERA assessment in Australia. It then discusses the role of journals in the codifying and dissemination of knowledge and how the adoption of citation based assessment changes the status of citations and changes citation behaviours. It is concluded that journals will continue to be important as an intermediary in knowledge creation.